Effect of Lifestyle on Coronary Artery Disease in Patients Presenting at Doctors Hospital, Lahore - Imdad, Seema; Mehmood Alvi, Farrakh; Kousar, Naheeda; Shuja, Fatima (Journal of Nutritional Therapeutics, 2017)
Objectives: To study the effect of lifestyle on coronary artery disease and to identify the strength of association between coronary artery disease and lifestyle factors among patients belonging to upper class of Lahore. Method: Seventy-two cases and 72 controls were recruited using convenient purposive sampling technique. Dietary pattern, activity level and socio-demographic profile were assessed with well-designed interview questionnaire. Results: According to statistical analysis of dietary factors, consumption of red meat, bakery products, restaurant food, fast food, soft drinks showed significant association with disease, whereas role of fruits and vegetables was found protective. Use of desi ghee had no significance in causing CAD in current study. Results of BMI and hip-waist ratio showed insignificance. Activity level was also insignificant while smoking and stress were significant. In socio demographic profile, sex of the respondents showed that 68.1% were male and 31.9% were females having CAD, so it was also statistically significant that heart diseases were more in males. Married individuals also showed significant result. Conclusion: According to results, consumption of red meat, bakery products, restaurant food, fast food, soft drinks showed significant association with disease, whereas role of fruits and vegetables was found protective. Whole wheat, desi ghee had no significance in causing CAD in current study. Results of BMI and hip-waist ratio showed insignificance. Activity level was also insignificant while smoking and stress was found to be associated. In socio demographic profile male sex, married individuals showed significant relation with CAD. Education, family type and income had no relation with heart disease in this study.